Influence of the trainings loading on the functional state of the cardiovascular system of sportsmen-armwrestling of different qualification. - Галашко [Galashko O. I.], Олександр Іванович (Slobozhanskyi Herald of Science and Sport, 2012)
Influence of the trainings loading is considered on the functional state of the cardiovascular system of sportsman-armwrestling of different qualification. The results of testing of frequency of heart-throbs are presented, and arteriotony of sportsman-armwrestling. Certainly, that the state of the cardiovascular system for more «successful» sportsmen arrives at maximal values during implementation of the special and base exercises, and after completion of training they return till about basic data